Price-setting hotel competition under uncertain demand - Ferreira, Fernanda A. (2019)
This paper considers a price-set competition between a nonprofit hotel and a for-profit hotel, in a differentiated service market, with uncertain demand. We compute the Bayesian-Nash equilibrium, and we analyse the effects of the degree of altruistic preference on market equilibrium outcomes. As a result, we get that as the nonprofit hotel values more the consumer surplus, both hotels set higher (resp., lower) prices, if the probability of higher demand is high (resp., low). Furthermore, the expected profit of the for-profit hotel decreases (resp., increases) with the degree of altruistic preference, for either low or high (resp., intermediate) values of this degree. The expectation of the objective function of the nonprofit hotel increases with the degree of altruistic preference.